2017
DOI: 10.1186/s12862-016-0857-z
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide scan for genes under balancing selection in Drosophila melanogaster

Abstract: BackgroundIn the history of population genetics balancing selection has been considered as an important evolutionary force, yet until today little is known about its abundance and its effect on patterns of genetic diversity. Several well-known examples of balancing selection have been reported from humans, mice, plants, and parasites. However, only very few systematic studies have been carried out to detect genes under balancing selection. We performed a genome scan in Drosophila melanogaster to find signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 92 publications
0
40
0
1
Order By: Relevance
“…; Hedrick ; Croze et al. ), the role of balancing selection in maintaining genetic diversity has been questioned. A recent study, however, has argued that because mutation and negative selection alone cannot explain the level of genetic and phenotypic variance observed in Drosophila , balancing selection needs to be invoked (Charlesworth ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…; Hedrick ; Croze et al. ), the role of balancing selection in maintaining genetic diversity has been questioned. A recent study, however, has argued that because mutation and negative selection alone cannot explain the level of genetic and phenotypic variance observed in Drosophila , balancing selection needs to be invoked (Charlesworth ).…”
mentioning
confidence: 99%
“…On the other hand, polymorphism is actively maintained under models of balancing selection, which refers to various polymorphism-promoting mechanisms such as overdominance (Pasvol et al 1978;Hughes and Nei 1988;Takahata and Nei 1990), spatially (Levene 1953) or temporally varying selection (Haldane and Jayakar 1963), and negative frequency-dependence due to resource competition (Roughgarden 1971;Dieckmann and Doebeli 1999;Ribeck and Lenski 2015). Because it is not clear whether assumptions of these models are satisfied for many loci in nature, and because some of their predictions, for example, an unusual elevation of heterozygosity at linked neutral sites (Charlesworth 2006) are not frequently observed (Asthana et al 2005;Hedrick 2006;Croze et al 2017), the role of balancing selection in maintaining genetic diversity has been questioned. A recent study, however, has argued that because mutation and negative selection alone cannot explain the level of genetic and phenotypic variance observed in Drosophila, balancing selection needs to be invoked (Charlesworth 2015).…”
mentioning
confidence: 99%
“…Balancing selection is indeed a selective process that actively maintains multiple variants of genes at frequencies larger than expected from genetic drift alone. Although not studied so far in D. suzukii, experimental evidence in several other Drosophila species (especially in D. melanogaster) confirms the maintenance of high level of variability in specific genomic regions through balancing selection (Charlesworth, 2015;Croze et al, 2017). Moreover, it has been reported that the level of variability in both marker loci and quantitative traits in laboratory populations can sometimes decline considerably less rapidly over time than is expected under the standard neutral model (e.g., (Gilligan, Briscoe, & Frankham, 2005) populations, associative overdominance due to strong linkage disequilibrium with sites under balancing selection can explain the maintenance of sequence variability in some genomic regions (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…Both theoretical and empirical works have recently suggested that enhanced neutral variability at nucleotide sites may be closely linked to sites under long-term balancing selection (i.e. sites for which heterozygous individuals have an advantage over homozygous individuals; (Croze et al, 2017;Gao, Przeworski, & Sella, 2015;Zhao & Charlesworth, 2016)). Balancing selection is indeed a selective process that actively maintains multiple variants of genes at frequencies larger than expected from genetic drift alone.…”
Section: Discussionmentioning
confidence: 99%
“…Si la correlación entre el locus y la condición es lo suficientemente fuerte, se puede mapear el gen que se asocia específicamente con un trastorno en una zona y un cromosoma específicos. Los marcadores genéticos usados en estudios de ligamiento se basan en polimorfismos de las secuencias de ADN (conocidos como SNPs por su sigla en inglés), es decir, variaciones comunes en la secuencia del ADN que generalmente no tienen ningún efecto funcional pero que, conociéndolas, pueden usarse para marcar la zona de un cromosoma en la que se encuentran 5,36 .…”
Section: Análisis De Ligamientounclassified